2015
DOI: 10.5811/westjem.2015.9.27298
|View full text |Cite
|
Sign up to set email alerts
|

Ready for Discharge? A Survey of Discharge Transition of Care Education and Evaluation in Emergency Medicine Residency Programs

Abstract: This study aimed to assess current education and practices of emergency medicine (EM) residents as perceived by EM program directors to determine if there are deficits in resident discharge handoff training. This survey study was guided by the Kern model for medical curriculum development. A six-member Council of EM Residency Directors (CORD) Transitions of Care task force of EM physicians performed these steps and constructed a survey. The survey was distributed to program residency directors via the CORD lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Prior to the pre-intervention phase of the study, the authors performed a thorough literature search 10 13 identifying essential components of a discharge conversation and incorporated this data with survey question outcomes data from the hospital site’s ED patient satisfaction survey provider (National Research Corporation Picker Survey, Lincoln, NE). Themes ascribed from this information led to a contributing authors’ consensus, which identified six essential components that should be addressed in a comprehensive discharge conversation (see Appendix 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior to the pre-intervention phase of the study, the authors performed a thorough literature search 10 13 identifying essential components of a discharge conversation and incorporated this data with survey question outcomes data from the hospital site’s ED patient satisfaction survey provider (National Research Corporation Picker Survey, Lincoln, NE). Themes ascribed from this information led to a contributing authors’ consensus, which identified six essential components that should be addressed in a comprehensive discharge conversation (see Appendix 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…After the pre-intervention phase of the study was completed, a 30-minute lecture consisting of a PowerPoint (Microsoft Corp., Redmond, WA) presentation with background information regarding what constitutes a comprehensive discharge 10 13 and introduction of “DC HOME” incorporating the six components of the comprehensive discharge plan was presented at the EM weekly didactic conference where all resident physicians were present. The lecture was followed by a practical, in which each resident present was paired with a co-resident.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…26,39 EM residency education has also found a lack of standardized approaches to training in transitions of care, in particular the ED to the inpatient handoff. [40][41][42] Although there are areas of overlap in EM and IM graduate medical education (GME) for the triagist role, such as interprofessional communication, we propose there are perspectives that are unique to IM GME. Systems-based thinking and understanding the health care system as it relates to the triagist role has not been defined or discussed in the literature.…”
Section: Curricular Competencies For the Triagistmentioning
confidence: 99%